Zinc air battery catalyst and preparation method thereof
By using nitrogen-doped carbon nanotube-loaded cobalt iron selenide catalyst in zinc air batteries, the problem of slow reaction kinetics of zinc air batteries is solved, efficient oxygen reduction and oxygen precipitation reactions are achieved, and catalytic activity and energy are significantly improved. Efficiency reduces costs.
Patent Information
- Application Number
- CN202411097315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The redox reaction and oxygen precipitation reaction of rechargeable zinc air batteries are slow, resulting in low round-trip energy efficiency and requiring the design of efficient dual-function catalysts, but the existing catalyst combination is complex and expensive.
Nitrogen-doped carbon nanotubes are used as the conductive network, and cobalt ferroalloy nitrogen-doped carbon nanosheets are loaded on the conductive carbon network to form nitrogen-doped cobalt ferrose selenide (N-CoFeSe2@NC@NCNTs) as zinc air battery catalyst, through the polymerization Pyrrole nanotube preparation, surface treatment, composite material preparation, carbonization and selenization treatment were obtained.
When the potential is below 0.6V, N-CoFeSe2@NC@NCNTs exhibit high limit current density, which is better than commercial Pt/C catalysts, and has an overpotential of only 339.5mV in terms of OER catalytic activity, which is better than commercial RuO2 catalysts , significantly improves the reaction kinetics and catalytic activity.
Smart Images

Figure CN119208631A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc-air battery catalysts, and particularly relates to a zinc-air battery catalyst and a preparation method thereof. Background Art
[0002] With the development of economy, people's excessive use of fossil energy has caused the depletion of fossil energy and a series of pollution problems. The development of new clean energy can effectively alleviate these problems. Among them, secondary batteries represented by lithium-ion batteries have been widely used as energy storage devices in life. However, due to the safety problems of lithium-ion batteries themselves and the small storage capacity of raw material lithium metal, the use of a large amount of lithium metal will inevitably cause a situation where lithium salts are in short supply. As a high energy density, excellent durability and clean and pollution-free zinc-air battery, it can effectively solve the problems of the above-mentioned lithium batteries. However, the multi-step electron transfer reaction kinetics of oxygen in the charging and discharging process of rechargeable zinc-air batteries are slow, resulting in low round-trip energy efficiency, which seriously restricts the development of rechargeable ZAB.
[0003] Rechargeable zinc-air batteries convert chemical energy and electrical energy into each other through redox reactions between the air electrode and oxygen. The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are two key steps, but the kinetics of the two reactions are very slow, and efficient bifunctional catalysts need to be designed. Currently, the best ORR catalyst is Pt-based catalyst, but Pt has poor OER activity. RuO2 and lrO2 are better OER catalysts, but their ORR performance is poor. Although the combination of these two catalysts can achieve bifunctional catalysis, it also leads to complex processes and high prices. Therefore, it is urgent to design an efficient bifunctional catalyst for use in rechargeable zinc-air batteries.
[0004] In recent years, single-atom catalysts (SACs) with maximum atomic utilization efficiency and high catalytic selectivity have shown significant advantages in the field of catalysis. A large number of experimental and theoretical results have shown that atomically dispersed transition metal-nitrogen-carbon (MNC) groups exhibit high catalytic activity and selectivity for ORR, and their ORR catalytic performance is comparable to that of current Pt-based materials. In particular, Co-NC shows obvious advantages in catalytic activity. However, the high loading of metal atoms is not conducive to the improvement of catalytic performance due to the high surface energy of metal atoms and their easy agglomeration. Metal-organic frameworks (MOFs) are conducive to the dispersion of metal atoms and the improvement of catalytic activity due to their unique porous structure and high specific surface area. Moreover, using MOF as a precursor, during the high-temperature calcination process, the nitrogen-containing ligands will be converted into negatively charged nitrogen-doped groups in the carbon substrate to coordinate and stabilize the target positively charged metal atoms. Therefore, some MOFs with high metal-nitrogen coordination content are widely used in the synthesis of SACs. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a zinc-air battery catalyst and a preparation method thereof, which has the characteristics of high specific surface area, multiple active sites and good electrochemical performance.
[0006] A zinc-air battery catalyst uses nitrogen-doped carbon nanotubes as a conductive network, and cobalt-iron alloy nitrogen-doped carbon nanosheets are loaded on the conductive carbon network to obtain nitrogen-doped cobalt iron selenide grown on the nitrogen-doped carbon nanotube network (N-CoFeSe2@NC@NCNTs) as a zinc-air battery catalyst.
[0007] A method for preparing a zinc-air battery catalyst specifically comprises the following steps:
[0008] (1) Preparation of polypyrrole nanotubes (PPy NTs): Polypyrrole nanotubes (PPy NTs) were prepared by dissolving ferric chloride hexahydrate (FeCl3·6H2O), methyl orange (MO) and pyrrole monomer.
[0009] (2) Surface treatment of polypyrrole nanotubes (p-PPy NTs): Surface treatment of polypyrrole nanotubes (p-PPy NTs) is performed using a surfactant and a dielectric barrier discharge to obtain surface treated polypyrrole nanotubes (p-PPy NTs).
[0010] (3) Preparation of Co-TCPP(Fe)@p-PPy composite material: Cobalt salt, pyrazine, PVP and p-PPy were mixed, and TCPP(Fe) dissolved in DMF and ethanol solution was added dropwise. The cobalt-based organic framework nanosheets prepared by the hydrothermal method were uniformly grown on the polypyrrole nanotubes, namely the Co-TCPP(Fe)@p-PPy composite material.
[0011] (4) Synthesis of CoFe@NC@NCNTs: Co-TCPP(Fe)@p-PPy composite material was carbonized and reduced in an inert gas atmosphere. After cooling, the nitrogen-doped carbon nanotube-loaded cobalt-iron alloy nitrogen-doped carbon nanosheets were collected and named CoFe@NC@NCNTs.
[0012] (5) Synthesis of N-CoFeSe2@NC@NCNTs: Using CoFe@NC@NCNTs as a precursor, selenium powder was placed upstream of a tube furnace and subjected to selenization and nitridation treatments in an Ar / NH3 RF plasma atmosphere. After cooling, nitrogen-doped cobalt iron selenide supported by nitrogen-doped carbon nanotubes was obtained and named N-CoFeSe2@NC@NCNTs.
[0013] Preferably, in step 1, the molar ratio of MO to FeCl3·6H2O is 1:10-1:15, the concentration of MO solution is 3mmol / L-6mmol / L, and the molar ratio of FeCl3·6H2O to pyrrole is 1:1.5-1:2.5.
[0014] Preferably, in step (1), the surfactant is sodium dodecyl sulfate, and the mass ratio of sodium dodecyl sulfate to polypyrrole nanotubes is 1:0.5-1:1.5.
[0015] Preferably, in step (2), the treatment conditions of the dielectric barrier discharge are a voltage of 70-80 V, a current of 50-100 mA, and a treatment time of 2-10 min.
[0016] Preferably, in step (3), the molar ratio of the cobalt salt to pyrazine is 1:1-2:1, the Co ion concentration is 1mmol / L-1.5mmol / L, the molar ratio of the cobalt salt to TCPP (Fe) is 5:1-1:1, and the amount of PVP is 1.5g / L-2g / L. The reaction temperature is 75-95°C and the reaction time is 18-32h.
[0017] Preferably, in step (4), the specific operation method is to heat from room temperature to a temperature of 300-400°C under an inert gas atmosphere for a period of time at a heating rate of 3-6°C / min, and keep at this temperature for 1-3 hours, then heat the furnace to a temperature of 700-900°C, and keep at this temperature for 1-3 hours. After cooling, the obtained black powder is washed with HCl aqueous solution, water, and ethanol, and then the black powder is collected by centrifugation and dried in an oven at 60°C to obtain a sample named CoFe@NC@NCNTs.
[0018] Preferably, in step (4), the inert gas is generally one or both of Ar or N2.
[0019] Preferably, in step (5), in an Ar / NH3 atmosphere, the temperature is raised from room temperature to 300-400°C at a rate of 3-6°C / min, and a radio frequency plasma discharge treatment is performed, the discharge power is 50-150W, and the pressure is 10-30Pa. The radio frequency plasma discharge treatment is performed at this temperature for 1-3h, and selenization and nitridation treatment are simultaneously performed. The amount of selenium powder is 10-20mmol, and the obtained sample is named N-CoFeSe2@NC@NCNTs. The beneficial effects of the present invention are:
[0020] 1. When the potential is lower than 0.6 V, the N-CoFeSe2@NC@NCNTs sample exhibits a high limiting current density higher than that of the commercial Pt / C catalyst, and the material has faster reaction kinetics in the ORR electrocatalytic process.
[0021] 2. At a current density of 10 mA cm -2 When the OER overpotential is 339.5 mV, the overpotential of the commercial RuO2 catalyst is 453.5 mV under the same test conditions. The N-CoFeSe2@NC@NCNTs sample prepared by the present invention has excellent OER catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0023] Figure 1 The microscopic morphology of N-CoFeSe2@NC@NCNTs prepared in Example 1 under a scanning electron microscope;
[0024] Figure 2 The linear sweep voltammetry test diagram (LSV) of oxygen reduction reaction (ORR) of Example 1, Comparative Example 1 and the comparative example sample;
[0025] Figure 3 The linear sweep voltammetry test diagrams (LSV) of the oxygen evolution reaction (OER) of Example 1, Comparative Example 1 and the comparative example samples are shown. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the following is a detailed description of the preparation method of a nitrogen-doped cobalt iron selenide catalyst (N-CoFeSe2@NC@NCNTs) grown on a nitrogen-doped carbon nanotube network and the beneficial effects of its application in zinc-air batteries in combination with the accompanying drawings and specific embodiments. The examples in this specification are only for explaining the present invention, not for limiting the present invention. The parameters, proportions, etc. of the examples are selected according to actual conditions and have no substantial effect on the results.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] Embodiment 1:
[0029] A method for preparing nitrogen-doped carbon nanotube-loaded nitrogen-doped cobalt iron selenide nanosheets (N-CoFeSe2@NC@NCNTs) comprises the following steps:
[0030] (1) Preparation of polypyrrole nanotubes (PPy NTs): 3.893 g of FeCl3·6H2O was dissolved in 240 mL of 5 mmol / L MO (methyl orange) aqueous solution. Then 1.2 mL of pyrrole monomer was added and magnetic stirring was performed at room temperature for 24 h. After the reaction, the solution was filtered and washed with anhydrous ethanol and ultrapure water until the solution was colorless, and then centrifuged to obtain a solid, which was dried in an oven at 60°C for 5 h to obtain polypyrrole nanotubes, which were labeled as PPy NTs.
[0031] (2) Dielectric barrier discharge surface treatment of polypyrrole nanotubes (PPy NTs): Weigh the mass of PPy NTs, then weigh half the mass of sodium dodecyl sulfate and dissolve it in ultrapure water, then add PPy NTs and methanol to the above solution. Use ultrasound to disperse the mixture for 3 hours, and after it is evenly dispersed, centrifuge the mixed solution to remove the lower precipitate, and then centrifuge the precipitate with methanol three times to remove the lower precipitate. Then dry it in an oven at 60°C for 5 hours to obtain the product, which is called S-PPy. S-PPy is treated with dielectric barrier discharge plasma at 75V, 55W for 5 minutes, and the resulting sample is recorded as p-PPy.
[0032] (3) Preparation of Co-TCPP(Fe)@p-PPy composite material: 0.0873 g of Co(NO3)2·6H2O, 0.016 g of pyrazine, 0.4 g of PVP and 0.025 g of p-PPy were dissolved in 240 mL of DMF and ethanol (V DMF :V 乙醇 =3:1) was placed in a 500 mL round-bottom flask and recorded as solution A. Then 0.1 mmol of TCPP(Fe) was dissolved in 80 mL of DMF and ethanol (V DMF :V 乙醇 =3:1) in a mixed solution, recorded as solution B. Then, solution B was added dropwise to solution A under stirring, and then the solution in the round-bottom flask was ultrasonically treated at room temperature for 10 minutes. After mixing evenly, the round-bottom flask was heated to 80°C and then kept reacting for 24 hours. After cooling, centrifugation was performed and then washed twice with ethanol, and dried in an oven at 60°C to obtain the Co-TCPP(Fe)@p-PPy composite material.
[0033] (4) Synthesis of CoFe@NC@NCNTs: Co-TCPP(Fe)@p-PPy was carbonized using a common quartz tube furnace, and 300 mg of dried Co-TCPP(Fe)@p-PPy was evenly distributed on the bottom of a ceramic boat. It was heated from room temperature to 300°C in an Ar atmosphere within 1 h. After being kept at this temperature for 2 hours, it was heated to 800°C at a rate of 5°C / min. At this temperature, it was kept for another 2 hours. After cooling, the black powder was washed with HCl aqueous solution, water, and ethanol. The black powder was then dried in an oven at 60°C to obtain a sample named CoFe@NC@NCNTs.
[0034] (5) Synthesis of N-CoFeSe2@NC@NCNTs: CoFe@NC@NCNTs were placed in a tube furnace, and the upstream of the CoFe@NC@NCNTs precursor contained 15.0 mmol of selenium powder. Then, in an Ar / NH3 atmosphere, RF plasma discharge treatment was carried out at 350°C with a heating rate of 5°C / min, a discharge power of 100 W, and a gas pressure of 20 Pa. The RF plasma discharge treatment was carried out at this temperature for 2 h to achieve selenization and nitridation at the same time. The final sample was named N-CoFeSe2@NC@NCNTs.
[0035] Bifunctional catalytic performance evaluation:
[0036] The electrocatalytic performance of the prepared samples was carried out using an electrochemical workstation (CHI760E) in a three-electrode setup.
[0037] Preparation of working electrode for ORR and OER performance test: Before using the rotating disk electrode (RDE), polish the glassy carbon electrode (GCE, d = 4.0 mm) to a mirror surface with a polishing cloth containing Al2O3 powder, then rinse it with distilled water, dry it at room temperature and set it aside. The powder sample needs to be configured into a slurry and applied to the glassy carbon electrode for testing. The slurry configuration method is: weigh 5 mg of the final powder sample prepared in Example 1 and add it to a mixed solution of 50 μL 5% Nafion solution and 950 μL isopropanol, and treat it in an ultrasonic cleaner for 20 minutes to form a uniform slurry. Add 10 μL for testing.
[0038] As a control experiment, a commercial 20wt.% Pt / C catalyst was selected in the ORR test, and the slurry preparation method was the same as that of the powder sample prepared in Example 1. 5mg of 20wt.% Pt / C powder was prepared into a slurry and evenly dripped on the electrode for testing. A commercial RuO2 catalyst was selected in the OER test, and the slurry preparation method was the same as that of the powder sample prepared in Example 1. 5mg of RuO2 powder was prepared into a slurry and evenly dripped on the electrode for testing. Electrochemical performance test: During the test, a standard three-electrode electrochemical test system was used, in which the counter electrode was a Pt sheet electrode, the reference electrode was a saturated calomel electrode (SCE) and the working electrode prepared as described above, and the test solution was a 0.1M KOH solution (pH=13). All potentials were calculated by referring to the reversible hydrogen electrode (RHE) through the Nernst equation: E(RHE)=E(Hg / Hg2Cl2)+0.2415+0.059pH. Before the linear sweep voltammetry (LSV) test, the working electrode was charged at 10mV s -1 The scan rate was activated by 50 cycles of CV and all electrochemical tests were performed at room temperature.
[0039] The LSV curves of ORR of N-CoFeSe2@NC@NCNTs sample prepared in Example 1 and commercial 20wt.% Pt / C catalyst in 0.1M KOH solution saturated with O2 at a rotation speed of 1600rpm were tested by rotating disk electrode (RDE). Figure 2 As shown in the figure, the onset potential and half-wave potential of N-CoFeSe2@NC@NCNTs are 1.0845 and 0.8245 V vs. RHE, respectively, and its electrocatalytic activity is similar to that of the commercial Pt / C catalyst tested under the same conditions (the onset potential and half-wave potential are 1.0965 and 0.8655 V vs. RHE, respectively). When the potential is lower than 0.6 V, the N-CoFeSe2@NC@NCNTs sample exhibits a high limiting current density of 5.7093 mA cm -2 , which is higher than that of commercial Pt / C catalyst (4.88 mA cm -2 ), indicating that the material has faster reaction kinetics in the ORR electrocatalytic process.
[0040] The OER catalytic activity was also tested under exactly the same conditions as the ORR test, and the commercial RuO2 catalyst was also tested under the same conditions as a comparative reference. Figure 3 As shown in the figure, the N-CoFe Se2@NC@NCNTs sample prepared in Example 1 has a current density of 10 mA cm -2When the OER overpotential is 339.5 mV, the overpotential of the commercial RuO2 catalyst is 453.5 mV under the same test conditions, indicating that the N-CoFeSe2@NC@NCNTs sample prepared in Example 1 has excellent OER catalytic activity.
[0041] Comparative Example 1: Nitrogen-doped carbon nanotubes loaded with cobalt-iron alloy nitrogen-doped carbon nanosheets (CoFe@NC@NCNTs)
[0042] (1) Preparation of polypyrrole nanotubes (PPy NTs): 3.893 g of FeCl3·6H2O was dissolved in 240 mL of 5 mmol / L MO (methyl orange) aqueous solution. Then 1.2 mL of pyrrole monomer was added and magnetic stirring was performed at room temperature for 24 h. After the reaction, the solution was filtered and washed with anhydrous ethanol and ultrapure water until the solution was colorless, and then centrifuged to obtain a solid, which was dried in an oven at 60°C for 5 h to obtain polypyrrole nanotubes, which were labeled as PPy NTs.
[0043] (2) Dielectric barrier discharge surface treatment of polypyrrole nanotubes (PPy NTs): Weigh the mass of PPy NTs, then weigh half the mass of sodium dodecyl sulfate and dissolve it in ultrapure water, then add PPy NTs and methanol to the above solution. Use ultrasound to disperse the mixture for 3 hours, and after it is evenly dispersed, centrifuge the mixed solution to remove the lower precipitate, and then centrifuge the precipitate with methanol three times to remove the lower precipitate. Then dry it in an oven at 60°C for 5 hours to obtain the final product, which is called S-PPy. S-PPy was treated with dielectric barrier discharge plasma at 75V, 55W for 5 minutes, and the resulting sample was recorded as p-PPy.
[0044] (3) Preparation of Co-TCPP(Fe)@p-PPy composite material: Co(NO3)2·6H2O (0.0873 g), pyrazine (0.016 g), PVP (0.4 g) and 0.025 g p-PPy were dissolved in 240 mL DMF and ethanol (V DMF :V 乙醇 =3:1) was placed in a 500 mL round-bottom flask and recorded as solution A. Then 0.1 mmol of TCPP(Fe) was dissolved in 80 mL of DMF and ethanol (V DMF :V 乙醇 =3:1) in a mixed solution, recorded as solution B. Then, solution B was added dropwise to solution A under stirring, and then the solution in the round-bottom flask was ultrasonically treated at room temperature for 10 minutes. After mixing evenly, the round-bottom flask was heated to 80°C and then kept reacting for 24 hours. After cooling, centrifugation was performed and then washed twice with ethanol, and dried in an oven at 60°C to obtain the Co-TCPP(Fe)@p-PPy composite material.
[0045] (4) Synthesis of CoFe@NC@NCNTs: Co-TCPP(Fe)@p-PPy was carbonized using a common quartz tube furnace, and 300 mg of dried Co-TCPP(Fe)@p-PPy was evenly distributed on the bottom of a ceramic boat. It was heated from room temperature to 300°C in an Ar atmosphere within 1 h. After being kept at this temperature for 2 hours, it was heated to 800°C at a rate of 5°C / min. At this temperature, it was kept for another 2 hours. After cooling, the black powder was washed with HCl aqueous solution, water, and ethanol. The black powder was then dried in an oven at 60°C to obtain a sample named CoFe@NC@NCNTs.
[0046] The LSV curve of ORR of CoFe@NC@NCNTs sample prepared in Comparative Example 1 was tested by rotating disk electrode (RDE) in 0.1M KOH solution saturated with O2 at a rotation speed of 1600rpm. Figure 2 shown.
[0047] The CoFe@NC@NCNTs sample prepared in Comparative Example 1 exhibited high ORR electrocatalytic activity, with an onset potential and a half-wave potential of 1.0545 and 0.8165 V vs. RHE, respectively. Its electrocatalytic activity was slightly lower than that of the N-CoFeSe2@NC@NCNTs catalyst prepared in Example 1 tested under the same conditions, but higher than that of the commercial Pt / C catalyst. The CoFe@NC@NCNTs sample exhibited a high limiting current density of 5.543 mA cm -2 , and still has excellent ORR catalytic activity.
[0048] The OER catalytic activity was also tested under exactly the same conditions as the ORR test, e.g. Figure 3 As shown in the figure, the CoFe@NC@NCNTs sample prepared in Comparative Example 1 has a current density of 10 mA cm -2 When , the OER overpotential is 387.5 mV, which shows excellent OER catalytic activity.
[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A zinc-air battery catalyst, characterized in that The structure of the invention is that nitrogen-doped carbon nanotubes are used as a conductive network, and nitrogen-doped cobalt iron selenide is loaded on the nitrogen-doped carbon nanotubes.
2. A method for preparing a zinc-air battery catalyst, characterized in that: The preparation method specifically comprises the following steps: (1) Preparation of polypyrrole nanotubes: Polypyrrole nanotubes (PPyNTs) were prepared by dissolving FeCl3·6H2O, MO, and pyrrole monomer; (2) Surface treatment of polypyrrole nanotubes: surface treatment of polypyrrole nanotubes using surfactant and dielectric barrier discharge to obtain surface treated polypyrrole nanotubes, i.e., p-PPy; (3) Preparation of Co-TCPP(Fe)@p-PPy composite material: Cobalt salt, pyrazine, PVP and p-PPy were mixed, and TCPP(Fe) dissolved in DMF and ethanol solution was added dropwise. The cobalt-based organic framework nanosheets prepared by the hydrothermal method were uniformly grown on the polypyrrole nanotubes, namely the Co-TCPP(Fe)@p-PPy composite material; (4) Synthesis of CoFe@NC@NCNTs: Co-TCPP(Fe)@p-PPy composite material was carbonized and reduced in an inert gas atmosphere, and then cooled, cleaned, and collected to obtain nitrogen-doped carbon nanotube-loaded cobalt-iron alloy nitrogen-doped carbon nanosheets named CoFe@NC@NCNTs. (5) Synthesis of N-CoFeSe2@NC@NCNTs: Using CoFe@NC@NCNTs as a precursor, selenium powder was placed upstream of a tube furnace and subjected to selenization and nitridation treatments in an Ar / NH3 RF plasma atmosphere. After cooling, nitrogen-doped cobalt iron selenide supported by nitrogen-doped carbon nanotubes was obtained and named N-CoFeSe2@NC@NCNTs.
3. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (1), the molar ratio of MO to FeCl3·6H2O is 1:10-1:15, the concentration of MO solution is 3mmol / L-6mmol / L, and the molar ratio of FeCl3·6H2O to pyrrole is 1:1.5-1:2.
5.
4. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (2), the surfactant is sodium dodecyl sulfate, and the mass ratio of the sodium dodecyl sulfate to the polypyrrole nanotubes is 1:0.5-1:1.
5.
5. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (2), the treatment conditions of the dielectric barrier discharge are voltage 70-80V, current 50-100mA, and treatment time 2-10min.
6. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (3), the molar ratio of the cobalt salt to the pyrazine is 1:1-2:1, the molar ratio of the cobalt salt to the TCPP (Fe) is 5:1-1:1, the Co ion concentration is 1mmol / L-1.5mmol / L, the amount of PVP is 1.5g / L-2g / L, the reaction temperature is 75-95°C, and the reaction time is 18-32h.
7. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (4), the specific operation method is to heat from room temperature to a temperature of 300-400°C under an inert gas atmosphere for a period of time at a heating rate of 3-6°C / min, and maintain this temperature for 1-3 hours, then heat the furnace to a temperature of 700-900°C, and maintain this temperature for 1-3 hours. After cooling, the obtained black powder is washed with HCl aqueous solution, water, and ethanol, and then the black powder is collected by centrifugation and dried in an oven at 60°C to obtain CoFe@NC@NCNTs.
8. The method for preparing a zinc-air battery catalyst according to claim 7, characterized in that: The inert gas is one or both of Ar and N2.
9. The method for preparing a zinc-air battery catalyst according to claim 2, characterized in that: In step (5), in an Ar / NH3 atmosphere, the temperature is raised from room temperature to 300-400°C at a rate of 3-6°C / min, and radio frequency plasma discharge treatment is performed. The discharge power is 50-150W and the gas pressure is 10-30Pa. The radio frequency plasma discharge treatment is performed at this temperature for 1-3h, and selenization and nitridation treatment are simultaneously performed. The amount of selenium powder is 10-20mmol, and N-CoFeSe2@NC@NCNTs is obtained.
10. A zinc-air battery catalyst, characterized in that: The method is prepared by any one of claims 2 to 9.
Citation Information
Patent Citations
Carbon nanotube, a supported catalyst comprising the same, and fuel cell using the same
CN101024495A
Metal chalcogenide heterogeneous binding unit site catalyst and preparation method thereof
CN114976067A
Transition metal-nitrogen / sulfur / selenium doped porous carbon catalyst and neutral zinc-air battery
CN115241577A
Nitrogen-doped carbon nano-tube loaded metal alloy nitrogen-doped carbon nano-sheet catalyst as well as preparation method and application thereof
CN116742023A
Preparation method and application of nitrogen-doped iron cobalt selenide / carbon nanotube composite electrode material
CN117912856A
Cited By
Iron-iron-phosphorus three-site electrocatalyst with asymmetric electronic structure and application of iron-iron-phosphorus three-site electrocatalyst
CN122136376A